Chemical composition and bioactivities of Melaleuca alternufolia essential oil and its main constituents against Spodoptera littoralis (Boisaduval, 1833) - Seham M. Ismail; Noura A. Hassan; Trandil F. Wahba; N. Shaker (Bulletin of the National Research Centre, 2022)
Highlights The chemical composition of M. alternifolia EO was identified by GC–MS. The EO of M. alternifolia and its components, terpinen-4-ol and γ-terpinene, had potent bioactivity against S. littoralis. M. alternifolia EO and their components, terpinen-4-ol and γ-terpinene have great potential as a biopesticide in integrated pest management programs.